Low dose gamma radiation on the keeping quality of minced beef - Jenifer P (Department of Livestock Products Technology, College of Veterinary and Animal Sciences, 2006)
Prevention of Food Adulteration Act (1954) as amended in 1998 has permitted irradiation at a dose rate of 2.5 to 4.5 kGy to control pathogenic microorganisms and to extend the shelf life of meat and meat products including poultry products. A study was conducted to evaluate the effect of low dose dose gamma irradiation on the various quality parameters of minced beef. The minced beef was prepared and packed in 200 g each in HDPE packets were subjected to irradiation either at 1.0, 2.0 and 3.0 kGy at melting ice temperature and kept at +4o C for further analysis on day 0, 7, 15, 21 and 30 or till spoilage whichever was earlier. The non spoiled samples were analyzed for its physicochemical, microbiological and sensory qualities. The keeping quality of minced beef was extended by 8-10 days at 1.0 kGy, 22-23 days at 2.0 kGy and 32-33 days at 3.0-kGy treatment, whereas the control samples were spoiled by 2- 3 days. With respect to physicochemical parameters, pH had no significant difference due to irradiation at different doses. On storage pH values decreased slightly without any significant difference between treatments. The WHC was significantly reduced in 3.0 kGy irradiated samples compared to control, 1.0 and 2.0 kGy samples on day of preparation and on storage by 7 days. The ability of minced meat to retain its water decreased gradually on storage and reached 50 per cent of its original value in 3.0 kGy treated and 30 days stored samples. The TBARS values which were nonsignificant due to irradiation on the day of preparation, increased as days of storage enhanced. The uniform increase with respect to higher dose of irradiation was noticed. The irradiation treatment had no significant effect on tyrosine values compared to control samples on day 0. As storage days increased, tyrosine values increased with significant changes among different treatments. The colour ‘L’values of the irradiated samples were nonsignificant compared to that of control and increased slightly as storage period extended. The ‘a’ and ‘b’ values were nonsignificantly decreased due to irradiation and storage. On the day of preparation the cooking loss among the different treatment groups were not significant and increased uniformily on storage. Irradiation had a beneficial effect on microbiological qualities of the minced beef. There was significant reduction in aerobic plate count at different doses of irradiation (1.0, 2.0 and 3.0 kGy). The initial counts gradually increased on storage. The coliform organisms were isolated from control and 1.0 kGy irradiated samples. There was about 63 per cent reduction in 1.0 kGy treated sample compared to that of control samples. All other irradiation doses (2.0 and 3.0 kGy) have totally destroyed coliform organisms in the minced beef and could not be detected throughout the storage period. None of the control samples or treated samples recorded E.coli and salmonella organisms. Like that of coliforms the faecal streptococci were found only in control and 1.0 irradiated samples. The treatment of minced beef meat by 2.0 and 3.0 kGy has totally destroyed the fecal streptococci and none of the samples had faecal streptococci during the storage period. The staphylococcal count was significantly reduced due to irradiation by 1.0, 2.0 and 3.0 kGy. It was found that organisms have multiplied and the number has increased as storage period enhanced. The organoleptic qualities of irradiated samples recorded a slightly higher nonsignificant scores compared to control for colour and flavour. The juiciness and tenderness were significantly higher in irradiated samples compared to control and 1.0 kGy treated samples. On storage all the sensory attributes scores were decreased and reaches the acceptable score around 6 in 30 days stored and 3.0 kGy irradiated samples. The irradiation preservation of minced beef was beneficial in saving the energy and time as the product can be chiller stored rather than in freezer. In addition irradiation could effectively control food borne illness by destroying the major pathogenic organisms without affecting the sensory and nutritional qualities of the product.